2007
DOI: 10.1097/bpo.0b013e31802b719b
|View full text |Cite
|
Sign up to set email alerts
|

Late Developmental Dislocation of the Hip After Initial Normal Evaluation

Abstract: Developmental dysplasia of the hip (DDH) denotes a wide spectrum of pathologies ranging from hip instability to frank dislocation. The current understanding is that cases of late diagnosis were missed during the newborn period. However, there is some evidence that a number of hip subluxations or dislocations may have been clinically stable in the neonatal period, but dislocate late. We present 5 cases of otherwise healthy children with normal physical examinations and hip radiographs in the first 3 months of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…Of the 17 children seeking treatment, 14 (82.4%) presented after age of 4 months. This late presentation is a problem also faced by orthopaedic surgeons in other developing countries 9,10 . There are no other reports of delayed presentation in Malaysia for comparison, but it is reasonable to believe that this is a common problem.…”
Section: Discussionmentioning
confidence: 94%
“…Of the 17 children seeking treatment, 14 (82.4%) presented after age of 4 months. This late presentation is a problem also faced by orthopaedic surgeons in other developing countries 9,10 . There are no other reports of delayed presentation in Malaysia for comparison, but it is reasonable to believe that this is a common problem.…”
Section: Discussionmentioning
confidence: 94%
“…Most cases of DDH in SA are diagnosed clinically, and a high quality clinical hip examination of newborns by a competent examiner remains a powerful tool. However, an early neonatal hip examination that finds nothing abnormal does not always preclude DDH at a later follow‐up 17 . Early discharge from hospital is a risk factor for late DDH in SA; previous research found a higher incidence when mother and child were discharged less than 4 days after the birth 4 .…”
Section: Discussionmentioning
confidence: 95%
“…However, an early neonatal hip examination that finds nothing abnormal does not always preclude DDH at a later follow-up. 17…”
Section: Resultsmentioning
confidence: 99%
“…NIH can normalize spontaneously (Gardiner and Dunn 1990, Rosendahl et al 1994, Bialik et al 1999). Also, cases of late-presenting DDH can be clinically and morphologically normal at birth (Lennox et al 1993, Raimann et al 2007) and even up to early school age (Modaressi et al 2011). Despite such possible crossover, early diagnosis and treatment of NIH clearly reduces the incidence of late DDH (Fredensborg 1976, Hansson et al 1983, Dunn et al 1985, Myers et al 2009).…”
mentioning
confidence: 99%